(3MeGjI CfXeI GdeYdheGJ (B/s - (3GdMejO, eMeO OHGSs; (3fjfh, eGQch GHQGgje s ((3YeGf(B: s (3OGQ GdMGeO ddfTQ h GdJhRjY(B, s, 2007)
(3jVe fXe GdeYdheGJ GdGOGQjI, Cef eQGcR GdeYdheGJ, GdLQGFe GdMGShHjI, ehGLgI GdchGQK, Cef GdHjGfGJ, Cef bhGYO GdHjGfGJ, Cef GdTHcGJ, ajQhSGJ GdMGSH GdBdjs
(3GdeQGLY U(B.189((3GbJfGAGJ (B2014 3(3f(B)s
Keywords: (3GdGOGQIs; (3GdLQjeI hGdeLQehfs; (3GdbQUfIs; (3fXe GdeYdheGJ(B- (3GdeDSSI GdeeJOI s